Comparison of information provided by pediatricians regarding tooth eruption and the information available on the internet - Maryam HajiAhmadi; Najmeh Akhlaghi; Faezeh Aghajani; Hadi Moshgelgosha; Mahshad Soltanian (Wolters Kluwer Medknow Publications, 2021)
Background: Most parents believe that teething is associated with some symptoms and commonly use Internet to gain more information about the health of their children. Pediatricians can also serve as a source of information for health-related requirements of parents. This study aimed to compare the information provided by pediatricians regarding tooth eruption and the information available in Persian-language websites. Materials and Methods: This descriptive, analytical, cross-sectional study was performed in two phases. In the first phase, the questionnaire was designed by 85 pediatric pediatricians in Isfahan about children's dental eruption and internet resources. The second phase was the study of 22 Persian websites about children's tooth eruption using Google search engine and the keywords "tooth eruption," "tooth eruption symptoms." Then a checklist was prepared to evaluate the quality and completeness of the content. Data were analyzed by the Chi-square test and Fisher's exact test using SPSS (P < 0.05). Results: None of the retrieved websites had the health on the net code of conduct. The most common symptoms of teething reported by both pediatricians and websites included irritability, drooling, gingival tenderness, chewing tendency, decreased appetite and sleep disturbances. In non-pharmacological methods to control the symptoms related to tooth eruption in both groups, embracing the baby (P < 0.001), using soft tooth ring (P = 0.049) and chewing hard foods (0.016 P = significant. Use of oral pain medication (P = 0.01) and sedatives and medications (P = 0.04) were significant in the medication method. Conclusion: None of the websites reviewed had a valid source code and author. Although websites cannot replace the instructions of pediatricians regarding growth and development of children and their teething, supplementary information can be acquired from high-quality websites because there seems to be no significant difference between these two information sources regarding tooth eruption symptoms and their management.